Fibula-first fixation in same-level distal third tibia and fibula fractures: A pilot randomized controlled trial - Gareth Ryan; Richard Buckley; Paul Duffy; Robert Korley; Ryan Martin; Kim Rondeau; Prism Schneider (Journal of Orthopaedic Surgery, 2025)
Introduction Fractures of the tibia and fibula occurring at the same level can be technically challenging. Fibular plating (FP) prior to intramedullary nailing (IMN) may facilitate tibial reduction, stabilization, and subsequent tibial healing. The primary goal of this study was to compare tibial fracture healing between FP and no fibular plating (NFP) in patients with same-level distal third tibia/fibula fractures. Methods Patients ≥18 years with distal third tibia/fibula fractures occurring at the same level were randomized to FP or NFP prior to infrapatellar IMN. Same-level fractures were defined as distal third tibia fractures with an ipsilateral supra-syndesmotic distal third fibula fracture. Intraoperative parameters, patient-reported outcome measures (PROMs), modified Radiographic Union Scale in Tibial fractures (mRUST) scores, radiographic alignment, and adverse events were recorded. Results 30 patients were recruited, with 15 randomized to each group. There were no differences in baseline characteristics between groups. Total operative time was longer in FP compared with NFP (105.5 vs 65.8 minutes, p = .001). Mean duration of fibular fixation was 28.1 minutes (SD = 11.9). There was no difference in duration of IMN; however, less time was required to pass the guidewire in FP (4.5 vs 11.8 minutes, p = .01). Patients in FP had higher mRUST scores at 6 months, lower incidence of delayed union, and shorter fibular time-to-union. There were no differences in alignment between groups. Conclusion Fibula-first fixation facilitated passage of the tibial guidewire and resulted in a modest improvement in the rate of tibia fracture healing. The results of this pilot study suggest that fibula-first fixation may be beneficial in patients with same-level distal third tibia/fibula fractures. Further research with larger sample sizes is needed to determine which patients may benefit most from fibula-first fixation.